Advances in Mechanical Design Proceedings of the 2017 International Conference on Mechanical Design (ICMD2017) - Tan, Jianrong; Gao, Feng.; Xiang, Changle; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
Focusing on innovation, these proceedings present recent advances in the field of mechanical design in China and offer researchers, scholars and scientists an international platform to present their research findings and exchange their ideas. In the context of the "Made in China 2025" development strategy, one central aspect of the ICMD2017 was Innovative Design Pushes "Made in China 2025." The book highlights research hotspots in mechanical design, such as design methodology, green design, robotics and mechanics, and reliability design, while also combining industrial design and mechanical design.
Mechanical Assembly Accuracy Analysis Considering the Actual Working Condition -- Thermodynamic Research on Flexible Bearing in Harmonic Drive -- Modeling the Behavior Process of Electromechanical Systems Based on Behavior Trees -- A CAD Model Retrieval System Based on Design Intent -- Simulation Research on Tool Temperature Field in High Speed Inner Cooling Milling -- Modal Optimization Analysis of Large-scale Modular Deployable Structure for SAR.
Keywords: Engineering design; Control engineering; Robotics; Automation; Industrial engineering; Production engineering; Engineering Design; Control, Robotics, Automation; Industrial and Production Engineering